1990
DOI: 10.1159/000163564
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, Culture, and Transplantation of Intrahepatic Biliary Epithelial Cells and Oval Cells

Abstract: Recent advances made in the isolation, culture, and transplantation of defined populations of intrahepatic biliary epithelial cells and oval cells have permitted direct analysis of the functions, growth properties, and differentiation potential of these respective cell types in their untransformed or transformed states. This review provides a current and comprehensive examination of the various approaches that have been taken to isolate and culture intrahepatic biliary epithelial cells from normal and cholesta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
69
0
3

Year Published

1992
1992
2011
2011

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 121 publications
(74 citation statements)
references
References 50 publications
2
69
0
3
Order By: Relevance
“…Agents that selectively stimulate bile duct proliferation do not induce oval-cell proliferation. Induction of bile duct hyperplasia by nonhepatocarcinogens such as bile duct ligation, 4,4'-diaminodiphenylmethane (DDPM), or a-naphthylisothiocyanate (ANIT) do not induce AFP or albumin-containing duct cells (75)(76)(77). There is one report identifying AFP-containing bile duct cells after ANIT (78), but this was not found in our studies (75,76 (50,75,76).…”
Section: Bile Duct Proliferationmentioning
confidence: 61%
“…Agents that selectively stimulate bile duct proliferation do not induce oval-cell proliferation. Induction of bile duct hyperplasia by nonhepatocarcinogens such as bile duct ligation, 4,4'-diaminodiphenylmethane (DDPM), or a-naphthylisothiocyanate (ANIT) do not induce AFP or albumin-containing duct cells (75)(76)(77). There is one report identifying AFP-containing bile duct cells after ANIT (78), but this was not found in our studies (75,76 (50,75,76).…”
Section: Bile Duct Proliferationmentioning
confidence: 61%
“…Proliferation of small AFP ϩ oval cells was first observed in primary cultures of liver cells isolated by gravity sedimentation from rats fed AAFsupplemented choline-deficient diets 2 ; similar results were reported with other such models. [28][29][30] Starting with rats fed ethionine in choline-deficient diets, 31 oval cell cultures were obtained that produced transformed cells after prolonged culture, 32,33 after transfection with oncogenes, [33][34][35] and after mutagenesis. [36][37][38] Many of these lines produced tumors when injected into nude mice.…”
Section: Discussionmentioning
confidence: 99%
“…Lines of liver epithelial (oval) cells have been developed which may serve as hepatocyte progenitors but differ morphologically from mature hepatocytes (29,(34)(35)(36). Recently it has been shown that human liver epithelial cells immortalized with simian virus 40 T antigen can express xenobiotic drugmetabolizing enzymes (37).…”
mentioning
confidence: 99%